PATH-13. THE ORIGIN OF HUMAN GLIOBLASTOMA (IDH WILDTYPE) IS NOT THE LOCATION OF THE TUMOR BUT THE SUBVENTRICULAR ZONE. (5th November 2018) - Kang, Seok-Gu; Ho Lee, Joo; Jin Yoon, Seon; Lee, Ji-Hyun; Hoon Kim, Se; Hyun Kim, Eui; Hee Chang, Jong; Ho Lee, Jeong
Abstract: Two hypotheses about the origin of human glioblastoma (GBM) genesis are known to be dedifferentiation of cancer cells and orthodox differentiation of cancer stem cells. However, little is known about whether the direction of the human GBM genesis begins at the site of the tumor or at the subventricular zone (SVZ) where normal neural stem cells (NSCs) are present. Here, we describe direct molecular genetic evidence from patient brain tissue and genome-edited mouse models that show astrocyte-like NSCs in the SVZ to be the cell of origin that harbors the driver mutations of human GBM. First, we performed deep sequencing of triple-matched tissues, consisting of i) normal SVZ tissue away from the tumor mass, ii) tumor tissue, and iii) normal cortical tissue (or blood), from 28 patients with GBM, isocitrate dehydrogenase-wild type (IDH-wildtype) or other types of brain tumors. In doing so, we found that normal SVZ tissue away from the tumor in 56.3% of GBM IDH-wildtype patients contained low-level GBM driver mutations (down to 1% of the mutational burden) that were observed at high levels in their matching tumors. Moreover, via single cell sequencing and laser microdissection analysis of patient brain tissue and genome editing of a mouse model, we discovered that astrocyte-like NSCs carrying driver mutations migrate from the SVZ and lead to the development of high-grade malignant gliomas in distant brain regions. Altogether, our results highlight NSCs in human SVZ tissue as the cell of origin that harbors the driver mutations of GBM. In addition, the origin of human glioblastoma is not the location of the tumor but the subventricular zone.